The results of crossing Hungarian yellow hens with different meat type cocks - Konrád, Szilárd; Kovácsné Gaál, Katalin; Bali Papp, Ágnes (Animal welfare, Ethology and Housing Systems (AWETH), 2007)
During our tests we have examined, whether the Hungarian yellow hens cross with different meat type cocks (S 77, Foxy chick, Redbro, Shaver farm, Hubbard flex) to create end-products are applicable for alternative broiler meat production. Out of the 5 genotypes the Hungarian yellow x Hubbard flex produced the biggest body weight (in mixed sex 2193 g) during the 84 days fattening, but because of the bad food conversation we rather aimed at Hungarian yellow x Foxy chick and Hungarian yellow x Redbro.Test slaughters of pure breed Hungarian yellow stock and the cross end-products fattened for 84 days 3–3 pullets and cockerels of average weight and 12–12 conventional broilers were carried out. The results have shown that the applied keeping technology significantly influenced some slaughtering parameters. The grill weight – live weight ratio came close the 72% while that of the pure breed Hungarian yellow was 62, and the cross-breed end-products was 61,3-67,9%. The same tendency can be seen at the breast weight in proportion to the grill weight (conventional broiler: 34,7; free-range: 23,6-26,9%). In contradiction the thigh weight in proportion to the grill weight in the free-range stock was 2,6-5,6% higher than that of the large scale broilers. At the animals fattened in the alternative keeping technology have significantly bigger gizzard and smaller quantity of abdominal fat in almost every case.
Keywords: Hungarian yellow; alternative keeping technology; crossing; test slaughter